2019
DOI: 10.1186/s11671-019-3093-9
|View full text |Cite
|
Sign up to set email alerts
|

ZnO/Cu2O/Si Nanowire Arrays as Ternary Heterostructure-Based Photocatalysts with Enhanced Photodegradation Performances

Abstract: Ternary ZnO/Cu 2 O/Si nanowire arrays with vertical regularity were prepared with all-solution processed method at low temperature. In addition to the detailed characterizations of morphologies and crystallographic patterns, the analyses of photoluminescence and photocurrents revealed the sound carrier separation owing from the established step-like band structures. By modeling the photodegradation process of the prepared heterostructures through kinetic investigations and scavenger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
(18 reference statements)
2
18
0
Order By: Relevance
“…It has been reported that the structures with metal pattern/dielectric layer/metal layer could proceeded the excellent photocatalytic oxidation of benzylamine [30]. In light of this finding, the present study unveiled the near-perfect and broadband light-absorption characteristics based on the simple sandwich-like design, and could be potentially used for efficient photocatalytic applications illuminated with visible light through replacing the middle SiO 2 layer with photochemical-active materials such as TiO 2 [30] or Cu 2 O [31], which might pave ways for organic synthesis, pollutant degradation and other photocatalytic applications.…”
Section: Discussionsupporting
confidence: 56%
“…It has been reported that the structures with metal pattern/dielectric layer/metal layer could proceeded the excellent photocatalytic oxidation of benzylamine [30]. In light of this finding, the present study unveiled the near-perfect and broadband light-absorption characteristics based on the simple sandwich-like design, and could be potentially used for efficient photocatalytic applications illuminated with visible light through replacing the middle SiO 2 layer with photochemical-active materials such as TiO 2 [30] or Cu 2 O [31], which might pave ways for organic synthesis, pollutant degradation and other photocatalytic applications.…”
Section: Discussionsupporting
confidence: 56%
“…The reductive photodegradation of methyl orange is also confirmed by the absence of the influence of isopropyl alcohol (IPA) on the photodegradation rate. IPA is one of the most widely used inhibitors of photocatalytic processes, due to its reaction with hydroxyl radicals [34]. Figure 11a shows time-resolved methyl orange absorption spectra during methyl orange photodecomposition by WO 3 @PVP sols both in deionized water and in a 20% IPA solution.…”
Section: Photocatalytic Dye Discolorationmentioning
confidence: 99%
“…As mentioned above, the increase in sodium concentration led to the formation of much more stable sodium tungsten bronzes and, subsequently, to the enhancement The reducing mechanism of photocatalytic activity of WO 3 @PVP nanoparticles was additionally confirmed by the introduction of HAuCl 4 in the reaction mixture. Here, the reduction of HAuCl 4 and the formation of gold nanoparticles was a competitive process and contributed to the organic dye discoloration rate [34]. Since the gold nanoparticles cause plasmon resonance effect, their absorption may interfere with the absorption of the methyl orange.…”
Section: Photocatalytic Dye Discolorationmentioning
confidence: 99%
“…The GO, GO AA and P25 TiO 2 samples followed a Langmuir–Hinshelwood mechanism during the photocatalysis ( Figure 10 B), which is indicated by the goodness of fitted line to the assumed pseudo first-order kinetics (Equation (1)). The behavior could be approximated by second-order kinetics ( Figure 10 C) as well (Equation (2)), with slightly better fitting [ 37 , 38 , 39 ]. The current and starting concentration of the dye is c and c 0 , respectively, A and A 0 is the measured and starting absorbance, k is the reaction rate constant and t is time, and the Lambert–Beer law holds true for these concentrations.…”
Section: Resultsmentioning
confidence: 99%